FUNGSIONAL BEVERAGES INSTANT GINGER POWDER (Zingiber officinale rosc)WITH THE ADDITION OF BULBULUS EXTRACT VARIATION (Eleutherine Americana Merr) AS NATURAL DYES - Rifkowaty, Encik Eko (The University of Lampung, 2015)
Antioxidant is a good compound for health because it scavenges free radicals in the body. The addition of bulbulus extract is expected to increase the antioxidant activity of the instant ginger powder. This study aimed to determine the effect of variation bulbulus extract addition on moisture content, reducing sugar, and antioxidant activity, as well asÂ preferency of instant ginger powder. Research was conducted using Completely Randomized Design (CRD) consisting of single factor with three (3) repeatitions. Organoleptic test was peformed on three attributes: namely color, taste, and texture. Result showed that the addition of bulbulus extract, Based on Anava and LSD test of the moisture content and reduction sugar, every treatment was significantly different. However, teh treatment did notÂ significant affect on the antioxidan activity. GC-MS analysis, enriched with bulbulus extract show that instant gnger powder it is assumed that the variation of of bulbulus extract addition bubulus extract contain importantÂ of compounds such as eleuthherol (88,79 %), gingerol (1,18 %)and zingiberene( 10,03 %). Organoleptic test demonstrate that the addition of consumerKeywords: instant ginger powder, bulbulus extract, antioxidant, preferensi